2017
DOI: 10.1186/s13062-017-0178-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive multiscapes: an up-to-date metaphor to visualize molecular adaptation

Abstract: BackgroundWright’s metaphor of the fitness landscape has shaped and conditioned our view of the adaptation of populations for almost a century. Since its inception, and including criticism raised by Wright himself, the concept has been surrounded by controversy. Among others, the debate stems from the intrinsic difficulty to capture important features of the space of genotypes, such as its high dimensionality or the existence of abundant ridges, in a visually appealing two-dimensional picture. Two additional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…Adaptation usually occurs at a local scale, by fixing one or a few mutations that confer an immediate advantage to populations. The typical time subsequently spent in this metastable state (a local fitness maximum) can be so large that, in all likelihood, the global maximum is never observed, and this local maximum works in practice as the asymptotic mutation-selection equilibrium ( Catalán et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation usually occurs at a local scale, by fixing one or a few mutations that confer an immediate advantage to populations. The typical time subsequently spent in this metastable state (a local fitness maximum) can be so large that, in all likelihood, the global maximum is never observed, and this local maximum works in practice as the asymptotic mutation-selection equilibrium ( Catalán et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the dynamical framework of competition between networks, each phenotype represents now a distinguishable network characterized by its size, connectivity and fitness level. Connector links correspond to regions of apposition between the two networks, which exist in most cases (in particular when the two phenotypes considered are common) but are difficult to find if populations are finite due to the vastness of genotype spaces and NN [ 30 ]. Also, the connector links might join regions with similar fitness but different internal connectivity, or regions with different fitness, among many other possibilities.…”
Section: Punctuated Dynamics In Molecular Adaptationmentioning
confidence: 99%
“…This latter case seems to be much more common than previously thought, meaning that the co-option of promiscuous, secondary gene functions [ 29 ] is likely a common adaptive mechanism. From a formal viewpoint, therefore, the complexity of the GP map implies that fitness landscapes should be visualized as high-dimensional and interwoven sets of networks that unfold into multiple layers under environmental change [ 30 ]. New techniques, in particular the use of deep sequencing and powerful massive ways to evaluate the fitness of individual genotypes, represent a breakthrough in the empirical characterization of the complex genotype-to-phenotype-to-function relationship [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been recently suggested that the dominant view among biologists of a static fitness landscape as a succession of valleys and peaks may be misleading to explain many ob-servations in virus evolution. Instead, it has been suggested that an adaptive multiscape (Catalán et al 2017), or a time-fluctuating adaptive seascape (Mustonen and Lässig 2009), may provide a much better representation.…”
Section: Introductionmentioning
confidence: 99%